2022
DOI: 10.1186/s13046-022-02482-3
|View full text |Cite
|
Sign up to set email alerts
|

Hsa_circ_0000098 is a novel therapeutic target that promotes hepatocellular carcinoma development and resistance to doxorubicin

Abstract: Background Circular RNA (circRNA) is crucial to the progression of hepatocellular cancer (HCC). In addition, Mitochondrial calcium uniporter regulatory factor 1 (MCUR1) is commonly overexpressed in HCC to increase cellular ATP levels. Due to the highly aggressive characteristics of HCC, it is essential to identify new diagnostic biomarkers and therapeutic targets that may facilitate the diagnosis of HCC and the development of effective anti-HCC treatments. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Accumulating studies indicate that circRNAs are differentially expressed in HCC, and these differentially expressed circRNAs may play the role of biomarkers in cancer diagnosis and prognosis. 37 , 38 However, the molecular mechanisms for circRNAs in HCC are still largely elusive. Hence, we investigated the function and underlying mechanism of the upregulated circROBO1 expression in HCC by screening the differentially expressed circRNAs (DECs) between HCC tissues and paired nontumor liver tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating studies indicate that circRNAs are differentially expressed in HCC, and these differentially expressed circRNAs may play the role of biomarkers in cancer diagnosis and prognosis. 37 , 38 However, the molecular mechanisms for circRNAs in HCC are still largely elusive. Hence, we investigated the function and underlying mechanism of the upregulated circROBO1 expression in HCC by screening the differentially expressed circRNAs (DECs) between HCC tissues and paired nontumor liver tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al[ 35 ] showed the potential diagnostic value of circ_0000098 in HCC, with an area of 0.829 under the receiver operating characteristic (ROC) curve. Further in vivo and in vitro experiments showed that circ_0000098 could play an oncogenic role by regulating mitochondrial calcium uniporter regulatory factor 1 expression by sequestering miR-383 [ 35 ].…”
Section: Circrna: An Important Regulatory Factor In Hccmentioning
confidence: 99%
“…Li et al[ 35 ] showed the potential diagnostic value of circ_0000098 in HCC, with an area of 0.829 under the receiver operating characteristic (ROC) curve. Further in vivo and in vitro experiments showed that circ_0000098 could play an oncogenic role by regulating mitochondrial calcium uniporter regulatory factor 1 expression by sequestering miR-383 [ 35 ]. Inhibiting the expression of circ_0000098 in HCC cells could diminish doxorubicin (DOX) resistance by decreasing the levels of intracellular ATP and the expression of the ATP-dependent drug efflux protein P-glycoprotein (P-gp) [ 35 ].…”
Section: Circrna: An Important Regulatory Factor In Hccmentioning
confidence: 99%
See 2 more Smart Citations